Einfluss der Kompaktierung auf die Elektrodenmikrostruktur und elektrochemische Performance bei Lithium-Ionen-Zellen - Schmidt, Denny (Schriftenreihe des Instituts für Angewandte Materialien, Karlsruher Institut für Technologie, 2021)
In this work, the influence of compaction of LiNi1/3Co1/3Mn1/3O2 and graphite-based electrodes is characterized electrochemically at current rates between C/20 and 5C in a wide porosity range from uncompacted states to porosities < 20%. From the determined capacitances, gravimetric and volumetric considerations, among others, are presented in Ragone plots and correlated with the microstructural analysis findings.